2022
DOI: 10.1021/acs.nanolett.2c03287
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Driven Zero-Field Near-10 nm Skyrmions in Two-Dimensional van der Waals Heterostructures

Abstract: Magnetic skyrmionslocalized chiral spin structuresshow great promise for spintronic applications. The recent discovery of two-dimensional (2D) magnets opened new opportunities for topological spin structures in atomically thin van der Waals (vdW) materials. Despite recent progress in stabilizing metastable skyrmions in 2D magnets, their lifetime, essential for applications, has not been explored yet. Here, using first-principles calculations and atomistic spin simulations, we predict that compressive strain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 63 publications
1
34
1
Order By: Relevance
“…The extracted |D| is about 1.5 mJ/m 2 at γ = −3%, which is comparable to the value previously estimated in FM/HM thin-film systems [12,18,47,49]. Such a large DMI indicates that the FGT/Ge heterostructure can be a promising interface for stable isolated skyrmions [58]. A more detailed analysis shows that the enhancement of the DMI in FGT/Ge is mainly mediated by the geometrical change due to the buckled structure of germanene (see Sec.…”
Section: Strainsupporting
confidence: 83%
See 2 more Smart Citations
“…The extracted |D| is about 1.5 mJ/m 2 at γ = −3%, which is comparable to the value previously estimated in FM/HM thin-film systems [12,18,47,49]. Such a large DMI indicates that the FGT/Ge heterostructure can be a promising interface for stable isolated skyrmions [58]. A more detailed analysis shows that the enhancement of the DMI in FGT/Ge is mainly mediated by the geometrical change due to the buckled structure of germanene (see Sec.…”
Section: Strainsupporting
confidence: 83%
“…However, the MAE is dramatically reduced to 25% of its original value at a compressive strain of γ = −3%. In connection with the exchange frustration in FGT/germanene, these large changes in the DMI and MAE open the possibility of zero-field magnetic skyrmions [58]. For the DMI in FGT/Ge, the three theoretical approaches are in good qualitative agreement, and we also discuss the quantitative comparison in detail.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…van der Waals heterostructures (vdWHs), which are vertically stacked by two 2D materials, have been considered to be promising candidates for optoelectronic devices, photocatalysis, and spintronics. Inspired by the traditional 2D vdWHs, researchers have theoretically proposed various heterostructures based on Janus 2D materials to explore their novel properties. In recent years, Janus vdWHs have been widely studied and classified into three categories: Janus TMDs–TMDs, , Janus TMDs–graphene, , and heterostructures composed of Janus TMDs and other traditional 2D materials. Many studies have found that these Janus vdWHs exhibited promising potential in terms of electronic properties, photocatalytic properties, Rashba effect, and piezoelectric effect.…”
Section: Introductionmentioning
confidence: 99%
“…Different spin textures have been previously observed in vdW magnets (e.g., Fe 3 GeTe 2 , CrCl 3 , Cr 2 Te 3 , Fe 5 GeTe 2 , CrGeTe 3 ). They range from magnetic bubbles 11,31,32 and stripe domains 33 , up to topological quasiparticles, such as skyrmions [34][35][36][37][38][39][40] and merons 2,41 , as recently summarised in the 2D Magnetic Genome 1 . These evidences provide a broad territory for exploration either in more fundamental levels or in functional applications where the control of spin textures in device platforms is the ultimate step.…”
Section: Introductionmentioning
confidence: 99%